HUBUNGAN PENGETAHUAN IBU DAN SOSIAL EKONOMI TERHADAP STATUS GIZI ANAK USIA DINI DI PAUD - Hasanah, Laeli Nur; Lestaluhu, Santi Aprilian; Mauludiyah, Zaida; Khodija, Unziya; Anwar, Rina (Ensiklopedia of Journal, 2024)
Nutritional status is the state of the body as a result of food consumption and the use of nutrients. Distinguished between good, less and more nutritional status. initial survey on December 27, 2021 at Paud Hasnatul Hassanah Sungai Siput Village, Siak Kecil District, Bengkalis Regency in 2018. The number of students consists of 50 students. Of the 10 students studied who were well-nourished, 3 students were malnourished, 4 students were undernourished and 3 students were overnourished. The purpose of the study was to determine the relationship between maternal and socioeconomic knowledge on nutritional status in early childhood at Paud Hasnatul Hassanah Sungai Siput Village, Siak Kecil District, Bengkalis Regency. This study uses a type of quantitative research with a cross sectional design. The instrument in this study used a questionnaire. Univariate and bivariate data analysis using chi Square test. The results of the study were the majority of mothers had sufficient knowledge 40.0% and mothers with low socioeconomic 27.3%. There is a significant relationship between knowledge (P value = 0.000), socioeconomics (P value = 0.000) on the nutritional status of early childhood children at Paud Hasnatul Hassanah Sungai Siput Village, Siak Kecil District, Bengkalis Regency. It is recommended for mothers to increase knowledge by always attending counseling about health, especially nutritional status in children, as well as for health workers to further improve counseling for families, health counseling counseling, and increasing the number of children in the community.Keywords: Knowledge Level, Socioeconomics, Nutritional Status